ABDURRAHMAN WAHID (GUS DUR) DAN MODERASI BERAGAMA: TRADISI DAN MODERNITAS DALAM MASYARAKAT INDONESIA - Kamila Zahrotinnisa; Adrianus Fani; Subaidi (Pascasarjana Universitas Al-Qolam Malang, 2025)
This journal aims to examine the harmonization of modern values without destroying the essence of religious teachings. The concept of religious moderation is the main foundation that must be applied in a pluralistic society. In the context of pluralistic Indonesia, religious moderation is expected to be a solution to radicalization conflicts and interreligious or interfaith intolerance. Gus Dur prioritized the importance of pluralism, tolerance, and dialogue as a way to build harmonious relations between religious communities. The method used in this research is a literature study, which analyzes various sources related to religious moderation. The results of the study show that religious moderation is not only important to create social harmony, but also as a strategy to maintain the integrity of the nation in facing the challenges of globalization and extremism. Thus, religious moderation could be the foundation for creating a peaceful and prosperous society, where tradition and modernity can co-exist.